GENERATE ASIAN GAMES 2018 MASCOT FOR BATIK MOTIF WITH NEURAL STYLE TRANSFER - Rakhmi Khalida (Moestopo International Review on Social, Humanities, and Sciences, 2022)
In the past, batik artists to create a batik motif required special skills and a long time because motif is the main element in batik, and the uniqueness of batik is from the motif itself. Recently computers were able to produce many ordinary images turned into works of art even producing a new motif variant product. The method used is neural transfer style based on CNN architecture. It has performed feature extraction on batik motifs and has produced variations of batik motifs from collaborations of existing batik motifs such as the kawung batik motif and Asian Games 2018 mascot image. Neural transfer style empowers people around the world to experiment with their own creativity seeing the importance of style transfer in the commercial arts world and how art exists in the real world Index Terms—CNN, Batik, Motif, Mascot, Silhouette.